Language Politeness Strategies in Instagram Comment Columns on Public Figures: A Pragmatic Study on Social Media User Interaction - Dina Aprilia; Musab Maina; Agus Mulyanto; Arif Firmansyah; N. Yeffa Afnita Apriliyani (Universitas Negeri Semarang, 2026)
The rapid development of digital communication has transformed public interaction patterns through platforms like Instagram. Instagram comment sections have become digital discursive spaces that demonstrate various forms of language use, including expressions of support, criticism, suggestions, and evaluations directed at public figures. This study aims to identify and analyze politeness strategies employed by netizens in Instagram comment columns discussing public figures from a pragmatic perspective. Using a qualitative descriptive-analytical approach with a purposive sampling technique, data were collected from Instagram comments directed at public figures during January–March 2026. Data were analyzed using Brown and Levinson's (1987) politeness theory framework, focusing on four strategy categories: bald on record, positive politeness, negative politeness, and off record. The results indicate that the positive politeness strategy was dominant, with a frequency of 52%, followed by bald-on-record and off-record strategies at 24% each, and negative politeness at 4%. Personal or family content tended to elicit positive responses, while public policy content more often drew direct criticism or sarcasm. This study makes theoretical contributions to cyberpragmatics research and enhances public awareness of the importance of language politeness in digital communication.